Bad painting good art. - Wien; Badura-Triska, Eva; Blistène, Bernard; Gelshorn, Julia; Gilman, Claire; Höller, Christian; Neuburger, Susanne; Neuner, Stefan; Petzel, Friedrich (Wien : Dumont Buchverlag Köln, 2008)
Baselitz, Georg ; Büttner, Werner ; Butzer, André ; Currin, John ; De Chirico, Giorgio ; Gallizio, Pinot ; Guston, Philip ; Jenney, Neil ; Jorn, Asger ; Kippenberger, Martin ; Magritte, René ; Morley, Malcolm ; Oehlen, Albert ; Picabia, Francis ; Polke, Sigmar ; Saul, Peter ; Schnabel, Julian ; Zimmer, Hans-Peter ; Spur Gruppe ; Sturm, Helmut ; Prem, Helmrad ; Yuskavage, Lisa
Bad Painting - good art, MUMOK (Museum Moderner Kunst Stiftung Ludwig), Wien, 2008-06-06. 2008-10-12
boek